HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN KESEHATAN MENTAL ANAK KELAS 5 DAN 6 DI SDN 01 NGOMBAKAN KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Budi Kristanto; Bagus Tesar Yunanto (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
AbstractBased Health Research (Riskesdas) in 2007, the national prevalence of mental emotionaldisorder in the population aged â‰¥ 15 years was 11.6%. The data indicate the numbers arequite large. Based on the observations of researchers one of the things that potentiallyassociated with children's mental health is the parents' parenting.This study aimed to determine the relationship of parenting parents with mental healthGrade 5 and 6 at SDN 01 Ngombakan Polokarto District of Sukoharjo district.Results of this research are (1) 34 respondents (74%) with democratic parenting, while 12parents of respondents (26%) with the authoritarian parenting, and no parents withpermissive parenting. (2) a total of 27 respondents (58%) in a healthy mental state, while19 respondents (42%) in an unhealthy mental state.The conclusion with Pearson Chi-Square is 0.0379, where <of Î±: 0:05. It can beconcluded that there is a relationship between parenting parents with mental healthGrade 5 and 6 at SDN 01 Ngombakan Polokarto District of Sukoharjo district.Keywords: Parenting, Mental Health, School Age